Pengaruh Kualitas Produk, Iklan, Elektronic Word Of Mouth Dan Citra Merek Terhadap Minat Beli Smartphone Oppo (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Papua) - Karina Monica Ersada Siagian; Louis S. Bopeng; Makarius Bajari (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
This study aims to determine the influence of product quality, advertisements, electronic words of mouth, and brand image on Oppo smartphone buying interests. This is a quantitative research with survey method. The population in this study are students of the Faculty of Economics and Business, Universitas Papua, with sample of 105 respondents, determined by the non-probability sampling technique. The analytical method used is the validity test and the reliability test using Cronbach's Alpha. The analysis technique used is the hypothesis and the multiple linear regression. The results of this study partially indicate that (1) a product quality has no effect on Oppo smartphone buying interest, as evidenced by the t-value of -0.662 and the significant value of 0.536 > 0.05, (2) advertisements have no effect on Oppo smartphone buying interest, as evidenced by the t-value of 1.067 and the significant value of 0.289 > 0.05, (3) electronic word of mouth has a positive effect on Oppo smartphone buying interest, as evidenced by the t-value of 4.999 and the significant value of 0.000 < 0.05, (4) and brand image has a positive effect on the Oppo smartphone buying interest, as evidenced by the t-value of 4.934 and the significant value of 0.000 < 0.05. The results of this study simultaneously indicate that product quality, electronic word of mouth and brand image have a positive effect on the buying interest of Oppo smartphone with a significant value of 0,000 < 0.005